Penerapan Konseling Individu dengan Teknik Cognitive Defusion dalam Mengatasi Overthinking - Ahmad Aldi; Komaruddin Komaruddin; Lena Marianti (Scidacplus, 2023)
The background of this research is that overthinking behavior makes clients always think about fears that may not necessarily happen, which results in feelings of trepidation in facing something that is considered dangerous for client A, UIN Raden Fatah Palembang student. So, it can be assumed about